'It's something you have to put up with'—service users' experiences of in utero transfer: a qualitative study. (7th January 2015) - Porcellato, L; Masson, G; O'Mahony, F; Jenkinson, S; Vanner, T; Cheshire, K; Perkins, E
Abstract : Objective: The purpose of this study was to gain in‐depth insight and enhance understanding of service users' experiences of the in utero transfer (IUT) process, in order to inform policy and improve the current service provision of maternal care. Design: Qualitative descriptive study using semi‐structured interviews. Setting: Participant's home or hospital in the Midlands, UK. Population: Fifteen women transferred in utero to a tertiary level maternity hospital; five male partners and two grandmothers. Methods: Audio‐recorded individual or paired semi‐structured interviews transcribed verbatum and analysed thematically using nvivo 9. Main outcome measures: Facilitators and barriers of the IUT experience. Results: Findings suggest that IUT is an emotional experience that financially disadvantages patients and their families. Male partners were perceived to be most negatively affected by the experience. The quality of the IUT experience was influenced by a range of factors, including the lack of proximity to home and the lack of information. Patients had little knowledge or awareness of IUT, and most felt unprepared for displacement. Despite this, there was resigned acceptance that IUT was a necessary rather than adverse experience. Conclusions: The experience of IUT for service users could be enhanced by ensuring that they are better informed about the process and the circumstances that necessitate displacement, that they are better informed about the hospital to which they are being transferred, and that they are transferred as close to home as possible. Efforts to minimise the emotional and socio‐economic impact of IUT on women and their families also need to be considered.